Amending the Sin Tax Law - Rosario G. Manasan; Danileen Kristel C. Parel (Philippine Institute for Development Studies (PIDS), 2013)
The amendment of the existing excise tax law on tobacco and alcoholic products is the only revenue measure that the Aquino administration has certified as urgent to date. This paper reviews and evaluates the different versions of both houses of the sin tax reform measure. Republic Act (RA) 10351, otherwise known as the Sin Tax Reform 2012, appears to have successfully put together the desirable provisions of the House and Senate version. RA 10351 not only simplifies tax administration and increases tax revenues, but also eliminates the preferential tax treatment given to existing brands by doing away with the freeze in price classification. However, earmarking of the incremental revenues, despite arguments against it, continues to be one of its major features.
Keywords: 330; reforms; Philippines; excise tax; cigarettes; sin tax; alcohol; tobacco